Prevalence of cardiovascular risk factors in a selected community at Kuantan, Pahang, Malaysia - Akter, Seikh Farid Uddin; Abdul Rani, Mohammed Fauzi; Nordin, Mohamad Sahari; Satwi, Sapari; Mohamed, Awang; Md Aris, Mohd Aznan; Draman, Samsul (Academic Journals, 2010)

(untitled)
Hypertension and obesity are established and independent risk factors for cardiovascular diseases. There are important inter-relationships between these two factors that may explain the aetiology of cardiovascular diseases. To determine the prevalence of hypertension and obesity in a rural community setting in Malaysia, and to identify their associated risk factors, a cross-sectional study was conducted among residents aged of 18 years and above at a Kampung, Kuantan, Pahang Darul Makmur, Malaysia from 2007 to 2008. Sample size was 219. Prevalence of hypertension was 35.6% (78), with the highest prevalence among those aged of 45 years and above (50.0%). The prevalence of hypertension was notably higher in males compared to females, (38.9 versus 34.0%). In addition, the prevalence of obesity was 54.8%, with the highest prevalence among those aged 55 to 64 years (66.7%). The obese respondents were at higher risk to be hypertensive (OR = 1.4, 95% CI = 0.744, 2.277). The prevalence of hypertension and obesity in this study was high which herald the need for prevention programs for these risk factors in such rural communities at Kuantan, Pahang Darul Makmur, Malaysia.